Explanation and elaboration of the Standards for UNiversal reporting of patient Decision Aid Evaluations (SUNDAE) guidelines: examples of reporting SUNDAE items from patient decision aid evaluation literature. Issue 5 (21st February 2018) - Hoffman, Aubri S; Sepucha, Karen R; Abhyankar, Purva; Sheridan, Stacey; Bekker, Hilary; LeBlanc, Annie; Levin, Carrie; Ropka, Mary; Shaffer, Victoria; Stacey, Dawn; Stalmeier, Peep; Vo, Ha; et al.
Abstract : This Explanation and Elaboration (E&E) article expands on the 26 items in the Standards for UNiversal reporting of Decision Aid Evaluations guidelines. The E&E provides a rationale for each item and includes examples for how each item has been reported in published papers evaluating patient decision aids. The E&E focuses on items key to reporting studies evaluating patient decision aids and is intended to be illustrative rather than restrictive. Authors and reviewers may wish to use the E&E broadly to inform structuring of patient decision aid evaluation reports, or use it as a reference to obtain details about how to report individual checklist items.